Fatal Injury of the Small Intestine during Retropubic Sling Placement - P. Kascak; B. Kopcan (Hindawi Limited, 2015)
We describe a case of injury of the small intestine in a patient who underwent placement of Align R retropubic urethral support system (BARD). Absence of characteristic symptoms of the bowel injury and peritonitis led to a rapid development of sepsis, multiple organ failure, and death. Although the placement of midurethral sling is a minimally invasive surgery, good diagnostic skills, proper evaluation of indications, safe performance of the procedure, and thorough postsurgical monitoring are paramount for safe and effective outcome of the surgery.